The protective effect of Morin against ifosfamide-induced acute liver injury in rats associated with the inhibition of DNA damage and apoptosis. (4th May 2022) - Özdemir, Selçuk; Kucukler, Sefa; Çomaklı, Selim; Kandemir, Fatih Mehmet
Abstract: Morin is a flavonoid and broadly found in white berry and cranberry branch. Ifosfamide (IFOS) is known as an anticancer and cytotoxic drug especially on the liver. This study aimed to explore the potential protective effects of Morin against IFOS-induced liver toxicity in rats. The model group of rats received a single injection of IFOS (500 mg/kg; i.p.) at day 2, whereas the protective groups of rats were given two different doses of Morin (100 and 200 mg/kg; given by gavage) at days 1 and 2. All animals were then culled 24 h post-IFOS injection. We observed that IFOS caused liver injury, oxidative stress, inflammation, DNA damage, and apoptosis. However, Morin decreased the levels of aspartate aminotransferase (AST), alkaline phosphatase (ALP), alanine aminotransferase (ALT) ( p  < 0.05). While Morin contributed to the recovery of superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), glutathione (GSH) levels, Morin decreased the levels of malondialdehyde (MDA) induced by IFOS in the liver ( p  < 0.05). Besides, the levels of nuclear factor kappa B (NF-κB), tumor necrosis factor-α (TNF-α), and P53 measured by ELISA test were reduced via Morin administration ( p  < 0.05). Lastly, the mRNA transcript levels of Bax, Apaf-1, Bcl-2, Bcl-xL, and inducible nitric oxide synthase ( iNOS ) determined by RT-PCR were down-regulated in the Morin groups ( p  < 0.05). These results indicate that Morin plays a protective role by reducing oxidative stress, inflammation, and apoptosis in the IFOS-induced liver injury in rats.